Is Saddle block superior to spinal anaesthesia for patients undergoing transurethral resection of prostate- a comparative evaluation - Kshetrapal, Kirti; Mishra, Priyanka; Kamal, Hemant; Bansal, Priyanka (Asian Journal of Medical Sciences, 2021)
Background: TURP is the most common surgical intervention for patients with benign prostatic hyperplasia. Aims and Objectives: This prospective randomized study was planned to evaluate spinal anaesthesia (SA) versus saddle block with regard to haemodynamic parameters, ephedrine consumption, patient and surgeon satisfaction, perioperative complications in patients undergoing TURP. Materials and Methods: Eighty patients between the ages of 50-80 years with BPH, belonging to ASA grade I- III, prostatic volume between 50 - 80 cc were included in our study. Patients were randomly divided into two groups of 40 patients each. Patients in group SA (n=40) received spinal anaesthesia and the patients in group SBBI (n=40) were given saddle block with bladder instillation of local anaesthetic jelly for undergoing TURP. Results: There was more statistically significant fall in MAP in Group SA as compared to Group SBBI (p<0.05). Complications like hypotension, bradycardia and vasopressor requirement was less but requirement (p=0.021) of supplemental analgesia was more in patients who were administered saddle block. There was significantly lower patient satisfaction in saddle block (p=0.044) but comparable surgical satisfaction in both groups. Conclusion: Both Spinal anaesthesia and saddle block are safe and effective techniques of anaesthesia for patients undergoing TURP. SA has advantages like less requirement of supplemental analgesia, longer duration of post-operative analgesia and more patient satisfaction. However, saddle block is superior to spinal anaesthesia with regard to haemodynamic stability; with less chances of hypotension, bradycardia and less vasopressor requirement. It is similar to SA in terms of providing adequate surgical conditions.